Plan de negocio para la producción y comercialización de pulpa de arándano en la ciudad de Catacocha, periodo 2023-2024 - Vivanco Hidalgo, Cristian Daniel (2024)
In this study focused on Catacocha, we sought to understand the preferences and consumption behaviors of blueberry pulp in order to enrich the development of a Business Plan for its production. The research, based on market methods, used a 17- question questionnaire applied to a representative sample of potential consumers in the region. The importance of adjusting product, pricing and marketing strategies based on the results obtained was highlighted, combining statistical and content analysis in an applied manner. In retrospect, the 'PULP-AR' project in Catacocha faced a challenging start with losses in its first cycles. However, as it progressed, a positive trend was observed in subsequent cycles, with revenue exceeding costs and generating profits, establishing a favorable benefit/cost ratio. Thoroughly identifying the causes behind initial losses was crucial to ensuring long-term sustainability. Detailed analysis revealed fluctuations in the project, highlighting the importance of implementing a strategic marketing plan. Periods with positive benefit/cost ratios coincided with increases in net benefits, underscoring the influence of effective promotion, including branding, advertising and community engagement strategies. The future viability of the project is linked to the ability to maintain and improve positive growth supported by effective execution of the marketing plan and lean financial management.